Enhanced Stability and Tunable Photoluminescence in Perovskite CsPbX3/ZnS Quantum Dot Heterostructure - Chen, Weiwei; Hao, Jiongyue; Hu, Wei; Zang, Zhigang; Tang, Xiaosheng; Fang, Liang; Niu, Tianchao; Zhou, Miao (Small (Weinheim an der Bergstrasse, Germany), 2017)
All‐inorganic perovskite CsPbX3 (X = Cl, Br, I) and related materials are promising candidates for potential solar cells, light emitting diodes, and photodetectors. Here, a novel architecture made of CsPbX3/ZnS quantum dot heterodimers synthesized via a facile solution‐phase process is reported. Microscopic measurements show that CsPbX3/ZnS heterodimer has high crystalline quality with enhanced chemical stability, as also evidenced by systematic density functional theory based first‐principles calculations. Remarkably, depending on the interface structure, ZnS induces either n‐type or p‐type doping in CsPbX3 and both type‐I and type‐II heterojunctions can be achieved, leading to rich electronic properties. Photoluminescence measurement results show a strong blue‐shift and decrease of recombination lifetime with increasing sulfurization, which is beneficial for charge diffusion in solar cells and photovoltaic applications. These findings are expected to shed light on further understanding and design of novel perovskite heterostructures for stable, tunable optoelectronic devices. A novel architecture made of perovskite CsPbBr3−xIx/ZnS quantum dot heterodimers is reported by material synthesis, characterization, optical measurements, and systematic first‐principles calculations. It is found that CsPbBr3−xIx/ZnS heterostructures exhibit high crystal quality, enhanced photostability, and tunable electronic properties, which may provide an exciting playground for future understanding and design of perovskite based nanostructures for high‐performance optoelectronic devices.